miR-128 Regulates Tumor Cell CD47 Expression and Promotes Anti-tumor Immunity in Pancreatic Cancer - Xi, Qing; Chen, Ying; Yang, Guang-Ze; Zhang, Jie-You; Zhang, Li-Juan; Guo, Xiang-Dong; Zhao, Jing-Yi; Xue, Zhen-Yi; Li, Yan; Zhang, Rongxin (Frontiers in Immunology, 2020)
Pancreatic adenocarcinoma (PDAC) is a highly fatal disease worldwide. MicroRNAs (miRNAs) could regulate the protein-coding RNAs related to tumor growth, invasion, and immune evasion. Therefore, the investigation of novel miRNAs may helpful to more effective therapies for PDAC. In this study, we investigated the role and mechanism actions of miR-128 in PDAC. By using bioinformatics methods, we found that decreased expression of miR-128 was associated with poor overall survival of PDAC. The miR-128 was inversely correlated with cluster of differentiation 47(CD47), which was positively related to zinc finger E-box-binding homeobox 1 (ZEB1) in PDAC. Through in vivo experiments, we found that miR-128 could suppress the growth and metastasis of PDAC. Analysis of the immune microenvironment demonstrated that overexpression of miR-128 on tumor cells could increase the percentages of dendritic cells (DCs), CD8+T lymphocytes, and natural killer T cells (NKT) in tumor and spleen, consequently enhancing anti-tumor immunity. In vitro assays showed that miR-128 could inhibit cell proliferation, clonogenicity, migration, and invasion in Panc02 cells and could also enhance the phagocytosis of macrophages and the activity of DCs. Western blot and qRT-PCR confirmed that miR-128 could regulate ZEB1 and further inhibit CD47 in pancreatic cancer cells. Therefore, we identified a novel regulatory anti-tumor mechanism by miR-128 in PDAC, which may serve as a novel therapy for PDAC.